Digital Game in Young Children's Numeracy Skill: An Innovation through Learning Media Development - Syarfina, Syarfina; Masruroh, Siti; Masyitah, Nur; Sahpitri, Yulia; Pratiwi, Aulia Desi (Universitas Nahdlatul Ulama Surabaya, 2023)
Children’s numeracy skills significantly influence their readiness to enter primary school. However, teachingnumeracy to children in concrete periods is still a big challenge for teachers. Moreover, technologybasedlearning media must still be considered appropriate for early introduction. This research aims todevelop an interactive digital learning media to improve early childhood numeracy skills. This Researchand Development (RD) method used the 4-D model, which consists of Defining, Designing, Developing,and Disseminating. Expert validators who test the feasibility of the product consist of material, media, andlanguage experts. Respondents in this study were ten children aged 4-5 years at PAUD Nurul Aisyah, EastAceh. The results showed that this digital game is feasible as a learning media to improve early childhoodnumeracy skills. The average validator score for product feasibility is in the very good category, andchildren’s numeracy skills are in the good category. With this learning media,